2022
DOI: 10.3390/ma15113938
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structure and Corrosion Resistance of Novel High-Entropy Alloys for Potential Biomedical Applications

Abstract: High-entropy alloys are a new generation of materials that have attracted the interest of numerous scientists because of their unusual properties. It seems interesting to use these alloys in biomedical applications. However, for this purpose, the basic condition of corrosion resistance must be fulfilled. In this article, selected corrosion properties of self-composed high-entropy alloys are investigated and compared with conventional biomedical alloys, that is titanium alloys and stainless steels. Corrosive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The corrosion potential (Ecorr), corrosion current density (Icorr), and polarization resistance (Rp) were obtained for each specimen according to both the polarization curve and the Tafel extrapolation method [32]. The corrosion rate of the corroded specimens was calculated from Faraday's law presented in the related literature [33,34]. FESEM examination was also performed to observe the corroded surface appearances of the specimens.…”
Section: Corrosion Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion potential (Ecorr), corrosion current density (Icorr), and polarization resistance (Rp) were obtained for each specimen according to both the polarization curve and the Tafel extrapolation method [32]. The corrosion rate of the corroded specimens was calculated from Faraday's law presented in the related literature [33,34]. FESEM examination was also performed to observe the corroded surface appearances of the specimens.…”
Section: Corrosion Testingmentioning
confidence: 99%
“…Additionally, some literature suggested that the corrosion rate can be calculated using the corrosion current density obtained from the polarization curves [33,34]. In this study, the corrosion rate of the specimens was determined according to the relevant literature, and the results are presented in Figure 15.…”
Section: Analysis Of Corrosion Behaviormentioning
confidence: 99%
“…It offers the opportunity to tackle the challenge, as it possesses the capability (high spatial resolution) to perform “pseudo-single-crystal” electrochemistry, which enables the execution of more precise and efficient research on the individual microstructure. For instance, the fusion line region in a dissimilar metal welded joint and specific microstructures of high entropy alloys, can be profoundly investigated using this technique. The obtained electrochemical properties of specific microstructures, such as the polarization curve of inclusions, can be employed as more accurate (the inclusions constitute all or most of the probed area) input conditions for finite element method (FEM) simulations of microgalvanic effect studies. , It is also an efficient way to verify the ab initio model based on density functional theory to evaluate the anisotropic anodic dissolution behavior (calculated polarization curves) of metals and alloys. , Furthermore, using SECCM is capable of performing high-throughput characterization on some samples (e.g., combinatorial materials chips and diffusion multiples) to efficiently obtain microelectrochemical big data for establishing a database concerning composition–structure–property relationships.…”
Section: Opportunitiesmentioning
confidence: 99%
“…The high-entropy alloy containing Cr, Ni, and Mo has an excellent corrosion resistance and can be used in the marine field [7]. High-entropy alloys can be utilized in biomedical applications due to their exceptional biocompatibility achieved through composition design [8,9].…”
Section: Introductionmentioning
confidence: 99%